OPTIMASI KOMPOSISI SETIL ALKOHOL DAN PROPILENGLIKOL PADA SEDIAAN LOTION TABIR SURYA EKSTRAK ANGGUR HITAM (Vitis vinifera L.) DENGAN METODE SIMPLEX LATTICE DESIGN - Elisabeth Oriana Jawa La; Fitriyani; Repining Tiyas Sawiji (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Black grapes have natural antioxidants which contain flavonoid compounds, namely resveratrol which acts as a UV absorbent so that it can be used as a sunscreen. To facilitate its use, cosmetic preparations are made in the form of lotions. The physical properties and stability of lotion preparations are influenced by emulsifiers and humectants which can maintain the water content when used. The aim of this study was to determine the composition of cetyl alcohol and propylene glycol to produce a formula with optimum physical properties and SPF value. This study used a laboratory experimental research design using the active ingredient of black grape extract (Vitis vinifera L.) at a concentration of 3%. The sunscreen lotion was made in 8 runs with a concentration range of 2-5% cetyl alcohol and 7-10% propylene glycol. The composition of cetyl alcohol and propylene glycol was optimized using Design Expert software version 13 with test parameters of spreadability, adhesion, and viscosity, as well as in-vitro SPF values ​​using a Uv-Vis spectrophotometer. The optimal formula is determined using a numerical method, then intelligence and re-tested its physical properties with predicted values ​​that have been set by the software. The results showed that the optimum formula for black grape extract lotion was 2.1% cetyl alcohol and 9.8% propylene glycol. Black grape extract lotion is in the form of a semi-solid dosage form, with a homogeneous light brown color, and a pH according to the skin. The optimum black grape extract lotion produced a spreading power value of 53.7 g.cm/minute, an adhesion of 1.4 seconds, a viscosity of 142 dPa.S, and an SPF value of 4.6. Based on the research, it can be concluded that the emulsifier and humectant components have an effect on the physical quality of the preparation, including viscosity, adhesion, spreadability.